Travel and tourism: an industry primer - Biederman, Paul S.; Lai, Jun; Laitamaki, Jukka M.; Messerli, Hannah R.; Nyheim, Peter D.; Plog, Stanley C. (New Jersey, 2008)
The book highlights the importance of travel and tourism to global economic and social vitality is explored.
Keywords: Tourism